PERAN MEDIA SOSIAL FACEBOOK DALAM PENINGKATAN JIWA BISNIS HIJAU PADA MAHASISWA DI KOTA MAKASSAR - Faizal Rizal Zaenal; Risma Haris; Sartika Sartika (UNM Environmental Journals, 2022)
The development of the digital world is increasingly important in the post-pandemic era, especially the use of social media which is the main factor in maximizing public awareness of the environment. Students as young people of change have a vital role in improving the nation's economy after the pandemic, one of which is by combining the interests of life economically and in a sustainable manner that are more concerned about world climate conditions. However, the reality is that young people have not maximized the use of social media for the benefit of the entrepreneurial world. The impact is that the level of green entrepreneurial spirit (Ecopreneur) among students is still quite low. Therefore, this study has the objectives (1) to describe the use of social media, especially Facebook, related to Ecopreneurs; (2) to determine the intensity of social media use Facebook per day. This research method is descriptive analysis, namely describing, analyzing and interpreting data. Data collection techniques by: observation, interviews, questionnaires and FGD (Focus Group Discussions) on 48 students. The results of the study show that Facebook social media users are increasingly massive among students to access information, namely Green Business (27%), Education (17%), Entertainment (50%) and the rest to access politics (6%). Meanwhile, the intensity of using Facebook social media per day is more than 4 hours per day (75%). The suggestions for students include: (1) Utilization of social media, especially Facebook related to green business literacy needs to be improved (2). The intensity of using Facebook social media should be put to better use by prospective entrepreneurs to get entrepreneurial opportunities such as: starting to open online stalls in the market place that has been provided by Facebook.